IMPLEMENTATION OF STEM EDUCATION IN DEVELOPING CRITICAL THINKING SKILLS IN JUNIOR HIGH SCHOOL STUDENTS: SYSTEMATIC LITERATURE REVIEW - Layli Alifia Syamsiandari; Sri Wahyuni; Sri Rejeki Dwi Astuti; Siti Shofa Assyifa'ul Qulbi Barid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the implementation of STEM education in enhancing critical thinking skills among junior high school students. The main issue addressed is the low level of students’ critical thinking ability. A Systematic Literature Review (SLR) following the PRISMA procedure was conducted, resulting in 13 relevant articles. The findings show that approaches such as PjBL-STEM, STEM-Design Thinking, flipped classroom, TPACK-STEM, and STEM-R effectively strengthen analysis, evidence evaluation, and problem-solving skills. STEM learning consistently improves students’ critical thinking despite challenges such as limited facilities and teacher readiness. The study concludes that STEM education is an effective strategy for developing critical thinking skills in junior high school students.